Analysis of the Influence of Work Stress and Workload on Employee Performance (Literature Review of Human Resource Management) - Tata Arya Cahyaaty; Reni Silviah (Siber International Journal of Sport Education, 2024)
Literature Review analysis of the influence of work stress and workload on employee performance is a scientific article with the aim of analyzing whether work stress and workload affect employee performance. The method uses a literature review approach, which aims to study and analyze various sources of literature related to the influence of employee performance, especially in the context of work stress and workload. The results of this article are: 1) Work stress affects employee performance, 2) Workload affects employee performance. Apart from these 2 exogenous variables that affect the endogenous variable of viral marketing, there are many other factors including work motivation, job satisfaction and organizational culture.